2009
DOI: 10.1002/jcb.22013
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid release by H2O2 mediated proliferation of mouse embryonic stem cells: Involvement of Ca2+/PKC and MAPKs‐induced EGFR transactivation

Abstract: Reactive oxygen species (ROS) generated by a variety of endogenous factors and roles in embryonic stem (ES) cells has yet to be identified. Thus, we examined role of arachidonic acid (AA) in H(2)O(2)-induced proliferation of mouse ES cells and its related signaling molecules. AA release was maximally increased in response to 10(-4) M H(2)O(2) for 1 h. In addition, H(2)O(2) increased intracellular Ca(2+) concentration ([Ca(2+)](i)) and the phosphorylation of protein kinase C (PKC), p44/42, p38 mitogen-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…PGE 2 was found to have a positive affect on the growth of hematopoietic stem cell progenitors obtained from zebrafish and mouse embryonic stem cells [84]. PTGS2 activity and PGE 2 have also been associated with mouse embryonic stem cell proliferation [85][86][87] and prevention of apoptosis [88]. These data are in agreement with our findings of increased PTGS2 activity and PGE 2 secretion in cells that are supportive of hESC growth.…”
Section: Discussionsupporting
confidence: 88%
“…PGE 2 was found to have a positive affect on the growth of hematopoietic stem cell progenitors obtained from zebrafish and mouse embryonic stem cells [84]. PTGS2 activity and PGE 2 have also been associated with mouse embryonic stem cell proliferation [85][86][87] and prevention of apoptosis [88]. These data are in agreement with our findings of increased PTGS2 activity and PGE 2 secretion in cells that are supportive of hESC growth.…”
Section: Discussionsupporting
confidence: 88%
“…Our data demonstrate that cPLA 2 α enhances ROS formation by MCAO (Figure 7) while others have shown that oxidative stress in mouse embryonic stem cells causes MAPK dependent phosphorylation of cPLA 2 α [49]. This interaction has the potential to form a positive feedback loop in which cPLA 2 α-dependent ROS increase kinase activation which leads to further cPLA 2 α activation.…”
Section: Discussionmentioning
confidence: 49%
“…faecalis induces cell proliferation through hydrogen peroxide-mediated EGFR activation. Several studies indicate that exposure to oxidative stress, such as the presence of H 2 O 2 , preferentially facilitates EGFR activation (38,58,59), enhances cell proliferation (43,57,70), and thereby promotes tumorigenesis (29). Because E. faecalis can generate a considerable amount of oxidants, such as superoxide and H 2 O 2 (30), our next series of experiments was designed to determine whether H 2 O 2 production by E. faecalis VF could induce cell proliferation via EGFR activation.…”
Section: High Frequency Of E Faecalis Infection In Oral Tumorsmentioning
confidence: 99%